Marketing factors and Twitter users’ behaviors of purchasing cosmetics via online social network in Mueang District, Chonburi Province - ungkanawin, Kittisak (Journal of Humanities and Social Sciences Loei Rajabhat University, 2018)
The purposes of this research study were to study and compare marketing factors and twitter users’ behaviors of purchasing cosmetics via online social network in Muaeng District, Chonburi province. The 383 samples who were twitter users in Mueang District, Chonburi provinces were purposively selected. The data was collected by using questionnaire and analyzed by using basic statistics as well as t-test One-way ANOVA and Chi-square. The results of the research were as follows. 1) The customers using twitter for making decision in purchasing cosmetics were single female undergraduate students with average income ranging from 10,000 – 20,000 Baht per month. 2) These customers normally used twitter for purchasing cosmetics during 7.00-12.00 p.m., averagely 1-4 hours a day, as well as for connecting with friends and others. 3) The comparison of 5 marketing factors and twitter users’ behaviors of buying cosmetics revealed that 3.1) customers spent different period of time and had different marketing factors regarding purposive service, products, and prices; on the other hand, there was no difference regarding other aspects; 3.2) customers’ behaviors regarding frequency of using the program and marketing factors of products and price of the products were different’; however, there was no difference regarding other aspects; 3.3) customers with different periods of time were not different in marketing factors in aspect of products, prices and marketing promotion and purposive marketing service, and 3.4) customers with different using purposes were not different in marketing factors in aspect of prices, marketing promotion, purposive marketing service. 4) The comparison of marketing factors in 5 aspects personal factors were found that, 4.1) marketing factor of customers with different genders was different while other aspects were not different; 4.2) for marketing factor in aspect of price, there was no difference found among customers with different genders, ages, marital statuses, educational levels and incomes; 4.3) marketing factors in aspect of marketing promotion showed that customers with different ages,educational level, occupations, and incomes were different, whereas, the customers with different genders and different marital statuses were not different, 4.4) marketing factors in aspect of purposive marketing service showed that customers with different occupations and different income were different but other factors were not different, and 4.5) marketing factors in aspect of privacy, it was found that customers with different genders, ages, marital statuses, educational levels, occupations, and incomes were not different.